The Application Practice of Computer Information Technology in Junior High School Chemistry Experiments Teaching - Meng, Lingbao (Journal of Educational Research and Policies, 2025)
The application of computer information technology in junior high school chemistry experimental teaching has significantly improved teaching effectiveness. Through virtual laboratories, multimedia displays, and other means, students can simulate complex experiments in a safe environment and intuitively understand chemical principles. The intelligent teaching system provides personalized learning paths and enhances learning motivation. At the same time, data analysis helps with precise evaluation and timely adjustment of teaching strategies. This practice not only enriches teaching methods but also promotes the cultivation of students’ innovation ability and practical skills.